MODEL STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENUMBUHKAN SCHOOL WELL-BEING PESERTA DIDIK SMP NEGERI 4 PEMALANG - Hadi Harnoto; Sitti Hartinah; Dewi Apriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Student well-being is a fundamental component in building a safe, supportive, and inclusive school environment that promotes holistic student development. However, observations at SMP Negeri 4 Pemalang indicate that the principal’s leadership still tends to be administrative and has yet to fully embrace a transformational approach focused on enhancing student well-being. This study aims to formulate a strategic model of transformational leadership by the school principal in fostering student well-being. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations, and documentation, and analyzed using an interactive model. The findings reveal that the principal has demonstrated two of the four core dimensions of transformational leadership—idealized influence and inspirational motivation—but has not yet fully developed the aspects of individualized consideration and intellectual stimulation. Quantitative data from student perception surveys show that emotional support received the lowest average score (2.9) compared to academic engagement (3.3) and learning comfort (3.2), indicating the need for a stronger psychosocial support system within the school. The study concludes that while a foundation for transformational leadership has been established, a broader strategic effort is needed—one that includes structured emotional support programs, capacity building for teachers, and active parental involvement. Such efforts are essential to realizing a school environment that not only educates but also nurtures student well-being in a sustainable and human-centered manner.